Association Between Glucocerebrosidase Mutations and Parkinson's Disease in Ireland - Olszewska, Diana A.; McCarthy, Allan; Soto-Beasley, Alexandra I.; Walton, Ronald L.; Magennis, Brian; McLaughlin, Russell L.; Hardiman, Orla; Ross, Owen A.; Lynch, Tim (Frontiers in Neurology, 2020)
Multiple studies implicate heterozygous GBA mutations as a major genetic risk factor for PD, however the frequency of mutations has never been examined in PD patients from the Irish population. We prospectively recruited 314 unrelated Irish PD patients (UK Brain Bank Criteria) and 96 Irish healthy controls (without any signs or family history of parkinsonism) attending The Dublin Neurological Institute (DNI). Complete exon GBA Sanger sequencing analysis with flanking intronic regions was performed. The GBA carrier frequency was 8.3% in PD, and 3.1% in controls. We identified a number of potentially pathogenic mutations including a p.G195E substitution and a p.G377C variant, previously described in a case study of Gaucher’s disease in Ireland. On genotype-phenotype assessment hallucinations, dyskinesia and dystonia were more prevalent in GBA-PD. The genetic etiology of PD in Ireland differs from the continental Europe as seen with the lower LRRK2 and higher than in most European countries GBA mutation frequency. Determining genetic risk factors in different ethnicities will be critical for future personalized therapeutic approach.